Psoriasiform Drug Eruption Associated with Sodium Valproate - Gulen Gul Mert; Faruk Incecik; Suhan Gunasti; Ozlem Herguner; Sakir Altunbasak (Hindawi Limited, 2013)
As psoriasis is a common skin disorder, knowledge of the factors that may induce, trigger, or exacerbate the disease is of primary importance in clinical practice. Drug intake is a major concern in this respect, as new drugs are constantly being added to the list of factors that may influence the course of the disease. We report a patient with a psoriasiform drug eruption associated with the use of sodium valproate. Physicians should be aware of this type of reaction. Early detection of these cases has practical importance since the identification and elimination of the causative drug are essential for therapy success.